Prevalence of drug resistance associated mutations in Plasmodium vivax against sulphadoxine-pyrimethamine in southern Pakistan - Raza, Afsheen (BioMed Central, 2013)
BACKGROUND: In Pakistan, Plasmodium vivax and Plasmodium falciparum co-exist and usage of sulphadoxine-pyrimethamine (SP) against P. falciparum exposes P. vivax to the drug leading to generation of resistant alleles. The main aim of this study was to investigate frequency distribution of drug resistance associated mutations in pvdhfr, pvdhps genes and provide baseline molecular epidemiological data on SP-associated resistance in P. vivax from southern Pakistan. METHODS: From January 2008 to May 2009, a total of 150 samples were collected from patients tested slide-positive for P. vivax, at the Aga Khan University Hospital, Karachi, or its collection units located in Baluchistan and Sindh Province. Nested PCR using pvdhfr and pvdhps specific primers was performed for all samples.91.3% (137/150) of the samples were tested PCR positive of which 87.3% (131/137) were successfully sequenced. Sample sequencing data was analysed and compared against wild type reference sequences. RESULTS: In dhfr, mutations were observed at codons F57L, S58R and S117N/T. Novel non-synonymous mutations were observed at codon positions N50I, G114R and E119K while a synonymous mutation was observed at codon position 69Y. In dhps, mutations were observed at codon position A383G and A553G while novel non-synonymous mutations were observed at codon positions S373T, E380K, P384L, N389T, V392D, T393P, D459A, M601I, A651D and A661V. CONCLUSION: This is the first report from southern Pakistan on SP resistance in clinical isolates of P. vivax. Results from this study confirm that diverse drug resistant alleles are circulating within this region.